2012
DOI: 10.5194/essd-4-31-2012
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-one years of mass balance observations along the K-transect, West Greenland

Abstract: Abstract.A 21-yr record is presented of surface mass balance measurements along the K-transect. The series covers the period 1990-2011. Data are available at eight sites along a transect over an altitude range of 380-1850 m at approximately 67• N in West Greenland. The surface mass balance gradient is on average 3.8 × 10 −3 m w.e. m −1 , and the mean equilibrium line altitude is 1553 m a.s.l. Only the lower three sites within 10 km of the margin up to an elevation of 700 m experience a significant increasing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 20 publications
7
85
0
Order By: Relevance
“…Observational records along the nearby K-transect have shown that the annual ELA has varied from ∼1400 to 1800 m (van de Wal et al, 2012). If the surface velocity and the ice sheet geometry are in a state of balance and reflect steady state flow dynamics over a decadal time scale across the study area, this implies that increased rates of sliding are sufficiently insensitive to seasonal variations in meltwater input so as to produce the observed ice geometry.…”
Section: Enhanced Basal Slipmentioning
confidence: 98%
See 1 more Smart Citation
“…Observational records along the nearby K-transect have shown that the annual ELA has varied from ∼1400 to 1800 m (van de Wal et al, 2012). If the surface velocity and the ice sheet geometry are in a state of balance and reflect steady state flow dynamics over a decadal time scale across the study area, this implies that increased rates of sliding are sufficiently insensitive to seasonal variations in meltwater input so as to produce the observed ice geometry.…”
Section: Enhanced Basal Slipmentioning
confidence: 98%
“…Meltwater-induced seasonal variations in ice motion have been observed to elevations reaching ∼1500-1600 m (Bartholomew et al, 2011;Palmer et al, 2011). Given this evidence, the long term measured ELA of 1553 m (van de Wal et al, 2012) appears to serve as a plausible limit of the inland extent of seasonal surface meltwater routing to the bed. Its location also aligns with the greatest rate of velocity change along the flowline (Figure 8), suggesting that the increase in velocity is related to the introduction of surface meltwater to the bed.…”
Section: Enhanced Basal Slipmentioning
confidence: 99%
“…Figure 9 illustrates the seasonal cycle for SMB and precipitation, runoff and melt components over both the 1961-1990and 1996-2008periods. For the 1961-1990 period, monthly SMB is generally positive, adding between 30 and 60 Gt to the ice sheet except for the peak melt period (June-August) where, despite increased precipitation, there is a net mass loss due to runoff.…”
Section: Seasonal Cyclementioning
confidence: 99%
“…The Regional Atmosphere Climate Model version 2.1 (RACMO2.1) was developed by the Royal Netherlands Meteorological Institute (KNMI) (van Meijgarrd et al, 2008). Adjustments specific to the Arctic environment have been made to the original model to produce RACMO2/GR.…”
Section: Racmomentioning
confidence: 99%
See 1 more Smart Citation